Image Building on European Security by France Through Military Officer Education Programme - Ariansyah, Helmy; Nugrahani, Henny Saptatia Drajati (UI Scholars Hub, 2024)
This study aims to explore image building activities carried out by France on European security through educational programs for military officers. In this education, military officers were envoys of various friendly countries of France. This military officers education is a forum where France can disseminate its national security vision and mission. France intension is to demonstrate its strong military traditions, as well as its solid doctrine and battle strategy in anticipation of regional and global threats. The programs offered by France in the education program are considered attractive to its partners. This study used participatory observation methods conducted to reconstruct the background, motivations, goals, and objectives of the French Government in providing education for military officers. In this study, the researchers are exploring the Nation Branding Theory by Simon Anholt and Keith Dinnie and its application in diplomacy specifically carried out by France, namely military officers education. The findings of this study show that France has strategically made the military officers education programs of its partner countries an instrument of foreign diplomacy in defense and security sec tors, in line with French national interests and France's geopolitical position in the European region and in the world. Keywords: France, European Security, Educational programme for military officers, Nation Branding Theory, military diplomacy